2017
DOI: 10.1111/kykl.12136
|View full text |Cite
|
Sign up to set email alerts
|

Donations to Political Parties: Investing Corporations and Consuming Individuals?

Abstract: Summary What motivates donations to political parties? Two views prevail. Donors are perceived either as ideologically motivated consumers or as privilege‐seeking investors. To investigate differences in donor motivation between corporations and individuals, we analyze data from Germany. For the period from 1994 to 2014, we find that corporations act more like investors than individuals do. First, we test whether corporations or individuals are more inclined to give more to incumbent parties than to parties ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 74 publications
2
4
0
Order By: Relevance
“…(). This line of evidence is in many respects consistent with the view of donations as a form of individual consumption (Fink, ).…”
Section: Hypothesis Developmentsupporting
confidence: 85%
See 1 more Smart Citation
“…(). This line of evidence is in many respects consistent with the view of donations as a form of individual consumption (Fink, ).…”
Section: Hypothesis Developmentsupporting
confidence: 85%
“…The incentivising effect of material incentives such as lottery tickets and symbolic rewards on blood donation is also documented in Costa-Font et al (2013), Goetter & Stutzer (2008 and Lacetera et al (2009). This line of evidence is in many respects consistent with the view of donations as a form of individual consumption (Fink, 2017).…”
Section: Iii1 Rewards and Prosocial Behavioursupporting
confidence: 85%
“…This theoretical claim has found support in empirical studies, showing that governing parties tend to enjoy higher incomes than opposition parties (Fink 2017;Lösche 1993). Furthermore, business donations have been found to be influenced by power status at the state level: Fink (2017), analysing private and business donors' spending patterns in the German states, showed that only corporate donors tend to give more to governing parties than to opposition parties.…”
Section: Party Financing In Federal Environmentsmentioning
confidence: 95%
“…For one, similarly to the incumbency effect in elections, governing parties may be more salient in the political debate, whereby they might be more likely to attract citizens’ attention than political actors on the opposition benches. Moreover, business actors could support the governing party also financially because they seek to maintain ties to the government, combined with the expectation of having access to the policy-making process to facilitate conducive policies for the business sector (Fink, 2017).…”
Section: Party Functions Competition and Campaign Expenditurementioning
confidence: 99%
“…There is also evidence that government parties receive more donations than opposition parties (Fink, 2017;Lo ¨sche, 1993: 222). For one, similarly to the incumbency effect in elections, governing parties may be more salient in the political debate, whereby they might be more likely to attract citizens' attention than political actors on the opposition benches.…”
Section: What Affects Parties' Campaign Spending Levels?mentioning
confidence: 99%